2021
DOI: 10.1002/adma.202006965
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Macroporous Superstructure of Nitrogen‐Doped Nanoporous Carbon Implanted with Ultrafine Ru Nanoclusters for Efficient pH‐Universal Hydrogen Evolution Reaction

Abstract: The massive depletion of fossil fuels has led to severe energy and environmental crisis, which urgently needs an in-depth research on the exploration of sustainable energy. Among various energy sources, hydrogen (H 2) is considered to be one of the most potential alternatives to traditional fossil fuels owing to its high energy density and environmental friendliness. [1] Electrochemical hydrogen evolution reaction (HER) is an attracting and scalable technology to split water into H 2 , which can use the renewa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
187
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 271 publications
(187 citation statements)
references
References 61 publications
0
187
0
Order By: Relevance
“…[28] The deconvoluted high-resolution spectra of the NMGO sample are given in Figure S3b, Supporting Information. It shows wellfitted four individual peaks, including oxidized N, pyridinic-N, pyrrolic-N, and graphitic-N. [27,29] It has been reported that pyridinic N content promotes synthesized catalyst's catalytic activity. [29] Further, rich pyridinic N contents can be served as active sites for anchoring single metal atoms.…”
Section: Single-atom Catalysts (Sac) Can Boost the Intrinsic Catalytic Activity Of Hydrogen Evolution Reaction (Her) And Oxygen Reductionmentioning
confidence: 93%
See 1 more Smart Citation
“…[28] The deconvoluted high-resolution spectra of the NMGO sample are given in Figure S3b, Supporting Information. It shows wellfitted four individual peaks, including oxidized N, pyridinic-N, pyrrolic-N, and graphitic-N. [27,29] It has been reported that pyridinic N content promotes synthesized catalyst's catalytic activity. [29] Further, rich pyridinic N contents can be served as active sites for anchoring single metal atoms.…”
Section: Single-atom Catalysts (Sac) Can Boost the Intrinsic Catalytic Activity Of Hydrogen Evolution Reaction (Her) And Oxygen Reductionmentioning
confidence: 93%
“…[25,26] It is reported that micropores in nanocarbon matrix are not very supportive towards mass transportation in terms of high current density. [27] Other reports suggest that the metal SAC case's acid leaching process opens maximum pores during the synthesis process to enlarge the surface area. Reports [25,26] evidenced that ordered mesopores are majorly hosting metal-doped (MNx) active sites for catalytic applications.…”
Section: Single-atom Catalysts (Sac) Can Boost the Intrinsic Catalytic Activity Of Hydrogen Evolution Reaction (Her) And Oxygen Reductionmentioning
confidence: 99%
“…For example, an ordered macro-meso-microporous and N-doped carbon superstructure anchored with a Ru nanocluster (Ru/OMSNNC) has been prepared by Xu and co-workers. [37] The SEM and TEM images show the macrochannels with the size of about 190 nm and surrounding walls of about 25 nm (Figure 10a). On the other side, the presence of a mesochannel and microchannel has been verified by the high N 2 absorption method and the average sizes are about 3.8 and 1.1 nm, respectively.…”
Section: Electrocatalysts Confined In Active Host Materialsmentioning
confidence: 99%
“…Ascribing to the optimal hydrogen binding energy provided by hydroxylated intermetallic Co 3 Mo and the high electron/ion transport property of the hierarchical porous skeleton, the overpotential at 10 mA cm À2 (Figure 10d) and Tafel slope of the Co 3 Mo-supported Cu skeleton (Co 3 Mo/Cu) were measured to be %12 mV and %40 mV dec À1 , respectively. In addition, current density as high [37] Copyright 2021, Wiley. c) Cross-sectional SEM image and d) HER LSV curves in 1 M KOH for Co 3 Mo/Cu, respectively.…”
Section: Electrocatalysts Confined In Active Host Materialsmentioning
confidence: 99%
See 1 more Smart Citation